Use of Different Animal Models in Prediction of Genetic Parameters of First Lactation and Herd Life Traits of Murrah Buffaloes - Singh, C V; Barwal, R S (Indian Journal of Dairy Science, 2012)
In order to compare different animal models, the methodology of mixed models under animal models was used to predict (Co) variance components of 8 traits related to production, reproduction and life time traits of 1312 Murrah buffaloes descendent from 122 Sires and 341 dams raised at four military dairy farm viz. Ambala, Agra, Lucknow and Bareilly. The phenotypic mean (LSD) of body weight at first calving, age at first calving, first lactation milk yield, herd life milk yield, first lactation period, first dry period, first calving interval and first service period were 497.86 ± 57.95 kg, 1267.04 ± 232.94 days, 1761.57 ± 506.91 kg, 5630.00 ± 1383.88 kg, 306.76 ± 65.39 days, 177.08 ± 96.19 days, 481.86 ± 126.21 days and 179.54 ± 125.61 days respectively. Additive variance (direct) component estimated for all the traits from univariate, model 2 and model 8 were not similar. Univariate RMEL analysis had higher values of additive variance for WFC, AFC, FLMY, HLMY, FLP, FDP, FCI and FSP than the estimate of model 2 and model 8. However, model 2 had lower values of additive vanances only for WFC than univeriate and model 8, but higher values for all other traits than univariate and model 8. Model 8 and univariate REML had similar values of environmental variances for all the traits but values estimated by model 2 were much lower than the other two models. The phenotypic variances estimated by model 2 and 8 univariate animal model were agreed for all the traits under study. The heritability estimates obtained under model 2 and univariate REML were found almost similar for all the traits while the heritability estimated under model 8 was low. The values for coefficient of variation estimated under different models were found to be almost similar. Genetic correlations among different traits ranged from very low to very high under model 2. Phenotypic and environmental correlations also showed same trend.